Pengaruh Pengetahuan Pajak, Kompleksitas Pajak, dan Biaya Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Karanganyar - Novi Yaya Riski Rohmadani; Fadjar Harimurti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Taxpayers who are compliant in paying their taxes will have a positive impact on state revenues for financing development. Tax Knowledge, Tax Complexity, and Tax Compliance Costs can help assess the level of Taxpayer Compliance in paying their Tax bills. This study aims to analyze the effect of Tax Knowledge, Tax Complexity and Tax Compliance Costs on Individual Taxpayer Compliance at the Karanganyar Pratama Tax Office. The population of this study was Corporate Taxpayers registered at the Karanganyar Pratama Tax Office with a total of 18,369 Individual Taxpayers. The sample in this study was part of the Corporate Taxpayers registered at the Karanganyar Pratama Tax Office which was calculated using the Isaac damn Michael formula as many as 80 Individual Taxpayers due to time constraints. The type of data used is quantitative data. The data source used is primary data. The sampling method used is random sampling, which is a sample technique that is selected randomly. The data collection technique uses the results of a questionnaire distributed to Individual Taxpayers. Data analysis techniques using descriptive statistical analysis, research instrument testing, classical assumption testing and hypothesis testing. The results show that Tax Knowledge and Tax Compliance Costs do not affect Corporate Taxpayer Compliance while Tax Complexity affects Corporate Taxpayer Compliance.